Upaya Meningkatkan Hasil Belajar Siswa dengan Menggunakan Metode Tutor Sebaya pada Pembelajaran Tari Kelas X1 SMA Negeri 5 Padang - Apridilla Limadi Putri; Susmiarti Susmiarti (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
2024 Efforts to Improve Student Learning Outcomes Using the PeerThis research aims to explain and describe efforts to improve student learning outcomes using the peer tutoring method in class X1 dance learning at SMA Negeri 5 PadangTutor Method in Class X1 Dance Learning at SMA Negeri 5 Padang. The type of research carried out was classroom action research (PTK) which was carried out in 2 cycles. The research subjects were 36 students of class XI.F1 SMAN 5 Padang. The data collection techniques used were observation, documentation and data analysis. The results of this research show that learning dance using the peer tutoring method was successful in improving the learning outcomes of class XI students at SMAN 5 Padang. It can be proven that before using the peer tutoring method, the average student score in cycle I was below the KKM, namely 70.5 with a KKM of 80. Meanwhile, in cycle II, student learning outcomes using the peer tutoring method increased by an average of 80.5. So it can be concluded that the application of learning through the peer tutoring method can improve student learning outcomes at SMAN 5 Padang.